Factors associated with mental health outcomes among caregivers of older adults in long-term care facilities during COVID-19 post-epidemic era in Shandong, China - Chen, Huiling; Cao, Yingjuan; Lu, Yanxia; Zheng, Xiaolei; Kong, Bin; Dong, Hua; Zhou, Qingbo (Frontiers in Psychiatry, 2022)
Background: COVID-19 pandemic has altered the work mode in long-term care facilities (LTCFs), but little is known about the mental health status of caregivers of older adults. Methods: A total of 672 formal caregivers of older adults in LTCFs and 1,140 formal patient caregivers in hospitals (comparison group) responded to an online survey conducted from March 25, 2022 to April 6, 2022. Five psychological scales, including Insomnia Severity Index (ISI), Generalized Anxiety Disorder-7 (GAD-7), Patient Health Questionnaire-9 (PHQ-9), The 5-item World Health Organization Well-being Index (WHO-5) and Perceived Stress Scale-14 item (PSS-14), were applied to assess participants’ mental health status. Factors, including sex, profession, marital status, economic conditions, length of working experience, frequent night shift beyond 1 day per week and having organic diseases, were included in logistic regression analysis to identify associated factors with mental health outcomes of formal caregivers of older adults in LTCFs. Results: Caregivers of older adults in LTCFs developed similar severe psychological symptoms with patient caregivers in hospital setting. For caregivers of older adults in LTCFs, unmarried status was a potent risk factor for insomnia, anxiety, impaired well-being and health risk stress, with odds ratios ranging from 1.91 to 3.64. Frequent night shift beyond 1 day per week was associated with higher risks of insomnia, depression and impaired well-being. Likewise, having organic disease or inferior economic condition, and being nurses appeared to be independent predictors for multiple mental health-related outcomes. Conclusions: During COVID-19 post-epidemic era, caregivers of older adults in LTCFs had a higher prevalence of psychological symptoms, especially those with particular risk factors. Special attention should be paid to promote their mental health.